Sjögren's syndrome associated dry eye in a mouse model is ameliorated by topical application of integrin α4 antagonist GW559090. (February 2016) - Contreras-Ruiz, Laura; Mir, Fayaz A.; Turpie, Bruce; Krauss, Achim H.; Masli, Sharmila
Abstract: Sjögren's syndrome is an autoimmune disease associated with inflammation of exocrine glands with clinical manifestations of dry eye and dry mouth. Dry eye in this disease involves inflammation of the ocular surface tissues – cornea and conjunctiva. While systemic blockade of adhesion molecules has been used to treat autoimmune diseases, the purpose of this study was to determine the therapeutic efficacy of topical application of an integrin α4 adhesion molecule antagonist in a mouse model of dry eye associated with Sjögren's syndrome. To assess this spontaneously developed ocular surface inflammation related to Sjögren's syndrome in TSP-1null mice (12 wks) was evaluated. Mice were treated with topical formulations containing 0.1% dexamethasone or 30 mg/ml GW559090 or vehicle control. Corneal fluorescein staining and conjunctival goblet cell density were assessed. Real-time PCR analysis was performed to assess expression of the inflammatory marker IL-1β in the cornea and Tbet and RORγt in the draining lymph nodes. Ocular surface inflammation was detectable in TSP-1null mice (≥12 wk old), which resulted in increased corneal fluorescein staining indicative of corneal barrier disruption and reduced conjunctival goblet cell density. These changes were accompanied by increased corneal expression of IL-1β as compared to WT controls and an altered balance of Th1 (Tbet) and Th17 (RORγt) markers in the draining lymph nodes. Topically applied dexamethasone and GW559090 significantly reduced corneal fluorescein staining compared to vehicle treatment (p = 0.023 and p < 0.001, respectively). This improved corneal barrier integrity upon adhesion molecule blockade was consistent with significantly reduced corneal expression of pro-inflammatory IL-1β compared to vehicle treated groups (p < 0.05 for both treatments). Significant improvement in goblet cell density was also noted in mice treated with 0.1% dexamethasone and GW559090 (p < 0.05 for both). We conclude that similar to topical dexamethasone, topically administered GW559090 successfully improved corneal barrier integrity and inflammation in an established ocular surface disease associated with Sjögren's syndrome. Highlights: We assess ocular surface inflammation in a mouse model of Sjögren's syndrome. Topical adhesion molecule blockade reduces ocular surface inflammation. Reduced local inflammation correlates with improved corneal barrier integrity. Local blockade of adhesion molecules is an effective strategy to treat dry eye.